The heterogeneity of negative problem orientation in Chinese adolescents: A latent profile analysis - Lin, Rong-Mao; Xiong, Xia-Xin; Shen, Yi-Lin; Lin, Nan; Chen, Yan-Ping (Frontiers in Psychology, 2022)
Negative problem orientation (NPO) has become an essential construct for comprehending social problem-solving deficits. However, the heterogeneity of NPO has not yet been explored. With a sample of Chinese adolescents (N = 2,174), four latent profiles were identified and characterized based on different levels of NPO: lower NPO, moderate NPO, self-inefficacy and negative outcome expectancy (SI&NOE), and dysfunctional NPO. Latent mixture modeling indicated a greater percentage of young boys in the SI&NOE and dysfunctional NPO profiles, and adolescents with dysfunctional NPO reported higher levels of worry, depressive symptoms, anxiety, and stress, and worse sleep quality. The implications of these findings are discussed herein.